2010
DOI: 10.1039/c0cc00777c
|View full text |Cite
|
Sign up to set email alerts
|

Exclusively selective oxidation of toluene to benzaldehyde on ceria nanocubes by molecular oxygen

Abstract: Well-defined ceria nanocubes covered by oleic acid with exposed {100} facets have been synthesized and exhibited exclusive selectivity for the oxidation of toluene to benzaldehydes in liquid phase by O(2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(61 citation statements)
references
References 27 publications
(21 reference statements)
2
59
0
Order By: Relevance
“…Moreover, shuttleshaped particles composed of closely packed ceria nanorods displayed higher activity for CO oxidation compared to ceria nanorods [34], which has been attributed to enhanced porosity, surface area and oxygen deficiency of these nanoshapes compared to ceria rods. Ceria nanocubes on the other hand displayed greater activity compared to nanoparticles of irregular morphology in selective oxidation of toluene and benzene oxidation [35]. Pure and supported ceria nanocubes exhibited twice higher activity in oxidation of hydrogen and ethanol compared to rods and particles [36,37].…”
Section: Introductionmentioning
confidence: 96%
“…Moreover, shuttleshaped particles composed of closely packed ceria nanorods displayed higher activity for CO oxidation compared to ceria nanorods [34], which has been attributed to enhanced porosity, surface area and oxygen deficiency of these nanoshapes compared to ceria rods. Ceria nanocubes on the other hand displayed greater activity compared to nanoparticles of irregular morphology in selective oxidation of toluene and benzene oxidation [35]. Pure and supported ceria nanocubes exhibited twice higher activity in oxidation of hydrogen and ethanol compared to rods and particles [36,37].…”
Section: Introductionmentioning
confidence: 96%
“…In addition, ceria nanomaterials also exhibit excellent catalytic properties in redox organic reaction. Lv et al [210] reported that CeO 2 nanocube with exposed (100) facets showed exclusive selectivity for the oxidation of toluene to benzaldehydes in liquid phase by O 2 . CeO 2 nanoplates prepared by Zhang et al can selectively catalyze the reduction of nitro-aromatic compounds [211,212].…”
Section: Catalysis Of Organic Chemistry Reactionsmentioning
confidence: 98%
“…The primary synthesis strategy is hydrothermal and/or solvothermal processes. 286,290,[292][293][294][295][296][297][298][299][300] Among them, a facile alkali-assisted hydrothermal process produced CeO 2 nanocubes of 20-50 nm (Figure 10.27), 280 and the sizes of the cubes could be further tailored in a wide range of 20-360 nm by simply adjusting the synthetic parameters. 293 But these cubes are too large to demonstrate appreciable effect in catalytic reactions.…”
Section: Ceo 2 -Np and Nanocubesmentioning
confidence: 99%
“…For example, ceria nanocubes with uniform sizes of about 5 nm and 10 nm were prepared using oleic acid as the structure-directing agent. 286,296,298 Recently, single-crystalline ceria nanocubes of about 10 nm with (100) facets were fabricated using a supercritical hydrothermal process. 299 This cubic nanostructure had surprisingly high extra-low-temperature OSC, demonstrating the potential to be a superior catalyst.…”
Section: Ceo 2 -Np and Nanocubesmentioning
confidence: 99%